2018
DOI: 10.1038/s41560-018-0233-x
|View full text |Cite
|
Sign up to set email alerts
|

Equity and the willingness to pay for green electricity in Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 51 publications
(51 reference statements)
2
15
0
2
Order By: Relevance
“…These technologies are currently financed by consumers via a surcharge on the electricity price, the so-called EEG levy, but firms in energy-intensive industries are allowed to pay just a small fraction of this levy, which in 2020 amounts to 6.76 cents per kWh. As a result of the industry exemptions, all other consumers have to pay a higher levy, frequently leading to claims of unfairness in the distribution of the costs of Germany's energy transition (Andor, Frondel, Sommer 2018). In 2018, 2,156 German firms benefitted from these exemption rules, while the remaining consumers had to bear a higher burden of about 5.5 bn euros in total (BAFA, BMWi 2019: 15).…”
Section: Liu 2004mentioning
confidence: 99%
“…These technologies are currently financed by consumers via a surcharge on the electricity price, the so-called EEG levy, but firms in energy-intensive industries are allowed to pay just a small fraction of this levy, which in 2020 amounts to 6.76 cents per kWh. As a result of the industry exemptions, all other consumers have to pay a higher levy, frequently leading to claims of unfairness in the distribution of the costs of Germany's energy transition (Andor, Frondel, Sommer 2018). In 2018, 2,156 German firms benefitted from these exemption rules, while the remaining consumers had to bear a higher burden of about 5.5 bn euros in total (BAFA, BMWi 2019: 15).…”
Section: Liu 2004mentioning
confidence: 99%
“…Unterschiede zur Bevölkerung gibt es auch in Bezug auf andere Merkmale: Ähnlich wie in anderen Studien sind höher Gebildete bei den teilnehmenden Haushalten überrepräsentiert (siehe Andor et al 2014Andor et al , 2017a2017b, 2018a, 2018b. So besitzen 44,3 % der befragten Haushaltsvorstände die (Fach-)Hochschulreife, während dieser Anteil in der Bevölkerung laut Mikrozensus bei lediglich 34,9 % liegt (Tab.…”
unclassified
“…Andor et al 10 have demonstrated that social justice in terms of burden-sharing for RES support cost is fundamental for the social acceptance of transitions towards more sustainable energy systems. However, we have demonstrated that lower-income households are most affected by electricity price increases including those caused by the introduction of RES levies.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, if increases in electricity prices are extreme, income inequality, as well as energy poverty and, with them, (perceived) social injustice, might eventually reach levels that are unacceptable for society. In case increases in electricity prices are primarily due to the support of RES, such as in Germany, and the distribution of the costs for RES support is perceived as unfair, societal support for the transition from fossil to renewable energy systems will eventually be at risk, as demonstrated by Andor et al 10 .…”
Section: Main Textmentioning
confidence: 99%